2017
DOI: 10.3389/fpubh.2017.00145
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Mentorship Program in Laos

Abstract: Skills strengthening and capacity building for maternal and newborn health (MNH) providers are essential to ensure quality care for mothers and newborns. There is, however, limited research regarding what constitutes an effective model in low-income countries. The Lao People’s Democratic Republic (Laos) has some of the region’s worst outcomes for neonatal and maternal mortality. Moreover, with a 23-year hiatus in midwifery training, which ended approximately 7 years ago, there is a cadre of new and inexperienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 22 publications
(28 reference statements)
1
17
0
Order By: Relevance
“…In addition, results revealed that knowledge and self-efficacy correlated moderately positive at pre-mentorship (r = 0.214) and strongly positive at post-mentorship ( r = 0.58) [ 24 ]. These findings are also consistent with the findings of other studies that have assessed mentorship programmes at both the facility and educational level and found that such mentorships are beneficial to the health providers and improve the quality of care delivery [ 13 – 15 , 21 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, results revealed that knowledge and self-efficacy correlated moderately positive at pre-mentorship (r = 0.214) and strongly positive at post-mentorship ( r = 0.58) [ 24 ]. These findings are also consistent with the findings of other studies that have assessed mentorship programmes at both the facility and educational level and found that such mentorships are beneficial to the health providers and improve the quality of care delivery [ 13 – 15 , 21 ].…”
Section: Discussionsupporting
confidence: 91%
“…Mentorship is a flexible teaching and learning process that serves specific objectives of the HCPs and health care services [ 13 – 15 , 21 ]. Given the disparities in maternal health services [ 22 ] and previous training programs that were provided to midwives, the TSAM project targeted staff providing care to women and newborns.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In high-income countries mentorship is considered essential to support the professional development of health professions faculty at all levels, and to role model professionalism for students in the health professions. Although research in LICs is limited, mentorship programs have been shown to improve quality of care [15][16][17]. Mentorship has been identified as a teaching and learning process that can assist HCPs working in a complex clinical setting to provide quality health care services [6,9,10,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Although research in LICs is limited, mentorship programs have been shown to improve quality of care [ 15 – 17 ]. Mentorship has been identified as a teaching and learning process that can assist HCPs working in a complex clinical setting to provide quality health care services [ 6 , 9 , 10 , 16 20 ]. A mentorship program could support HCPs in rural areas in ways that the traditional hierarchical supervision model does not.…”
Section: Introductionmentioning
confidence: 99%